Effect on Travel Distance of a Statewide Regionalization Policy for Initial Breast Cancer Surgery - Bickell, Nina A; Nattinger, Ann B; McGinley, Emily L; Schymura, Maria J; Laud, Purushottam W; Pezzin, Liliana E (Journal of clinical oncology, 2025)
Reimbursement strategies to regionalize care can be effective for improving patient outcomes but may adversely affect access to care. We sought to determine the effect on travel distance for surgical treatment of a 2009 New York State (NYS) policy restricting Medicaid reimbursement for breast cancer surgery at low-volume hospitals. From a linked data set merging the NYS tumor registry with hospital discharge data, we identified women younger than 65 years with stage I-III first breast tumors from pre- and post-policy periods. We classified patients by urbanicity of their residence into four geographic areas (New York City, other large urban core, suburban/large town, and small town/rural). A multivariable difference-in-difference-in-differences model was used to estimate the policy effect on the distance traveled by Medicaid and non-Medicaid insured patients before and after the policy, by area of residence. Among the 46,029 study sample, 13.5% were covered by Medicaid. Regardless of insurance, women treated more recently traveled longer distances to their surgical facility than those in the prepolicy period. Regardless of time period, Medicaid beneficiaries drove fewer miles to treatment than women with other insurance. Although all women traveled greater distances postpolicy, the increase was not significantly different by insurance status (Medicaid or not), except for those living in suburban areas in which Medicaid patients traveled further postpolicy (+7.7 miles compared with +3.4 miles for non-Medicaid; = .007). After a policy regionalizing surgical care, only suburban Medicaid patients experienced a statistically significant (albeit small) increase in travel distance compared with non-Medicaid patients. In the state of NY, regionalization of breast cancer care yielded improved outcomes with minimal decrease in access.